Importance of Examined Lymph Node Number in Accurate Staging and Enhanced Survival in Resected Gastric Adenocarcinoma—The More, the Better? A Cohort Study of 8,696 Cases From the US and China, 2010–2016 - Huang, Lei; Zhang, Xinyue; Wei, Zhijian; Xu, Aman (Frontiers in Oncology, 2021)
Background: While most guidelines advocate D2 lymphadenectomy for non-metastatic gastric adenocarcinoma (nmGaC), it is not always performed as standard of care outside East Asia. The recommended minimal examined lymph node (ELN) count in nmGaC to stage cancer accurately varies largely across guidelines, and the optimal count to satisfactorily stratify patient survival has yet to be determined. This large cohort study aimed at robustly defining the minimal and optimal thresholds of examined lymph node (ELN) number in non-metastatic gastric adenocarcinoma (nmGaC). Methods: Data on nmGaC patients operated in 2010-2016 and surviving ≥3 months were retrieved from the US SEER-18 Program and a Chinese multi-institutional gastric cancer database (MIGC). The correlation of ELN count with stage migration and patient survival were quantified with the use of the multivariable-adjusted logistic and proportional hazards Cox models, respectively. The sequences of odds ratios (ORs) and hazard ratios (HRs) for each additional ELN were smoothed, and the structural breakpoints were determined. Results: Together 7228 patients from the US and 1468 from China were analyzed, encompassing 23,114 person-years of follow-up. The mean ELN count was 20 in the US and 30 in China. With more ELNs, both cohorts significantly showed proportional increases from lower to higher nodal stage (ORSEER=1.03, 95%-CI=1.03-1.04; ORMIGC=1.02, 95%-CI=1.02-1.03) and sequential enhancements in postoperative survival (HRSEER=0.97, 95%-CI=0.97-0.97; HRMIGC=0.98, 95%-CI=0.97-0.99). Correlations for both stage migration and survival were still significant in most subgroups by patient, cancer, and management factors. Breakpoint analyses revealed a minimum threshold ELN count of 17 and an optimum count of 33, which were validated in both cohorts with good efficacy to differentiate probabilities of both stage migration and survival. Conclusion: In resected nmGaC patients with anticipated survival ≥3 months, more ELNs are correlated with more accurate staging, which may partly explain the survival correlation. This observational investigation does not indicate causality. Our findings robustly conclude 17 ELNs as the minimum and propose 33 ELNs as the optimum thresholds, to assess the quality of lymph node examination and to stratify postsurgical survival. Keywords: Gastric adenocarcinoma; examined lymph node count; accurate staging; stage migration; long-term survival; multivariable breakpoint analysis; large cohort study